Vancomycin-resistant enterococci carriage in an acute Irish hospital. Issue 2 (June 2016) - Whelton, E.; Lynch, C.; O'Reilly, B.; Corcoran, G.D.; Cryan, B.; Keane, S.M.; Sleator, R.D.; Lucey, B.
Summary: Background: Ireland has been shown to have the highest rate of vancomycin-resistant enterococci (VRE) in cases of bacteraemia in Europe, according to a report in 2014 from the European Antimicrobial Resistance Surveillance System Network. Aim: To investigate the prevalence of VRE gut colonization in a cohort of patients in 2014 at Cork University Hospital (CUH) by performing a cross-sectional study using faecal samples submitted to the microbiology laboratory for routine investigation from both hospital inpatients and community-based patients. Methods: Faeces were examined for VRE colonization using selective cultivation, antimicrobial susceptibility testing, and speciation using matrix-assisted laser desorption ionization time-of-flight mass spectrometry. All VRE isolates were evaluated by molecular means for resistance determinants, type, and Insertion Sequence 16 as an indicator of Clonal Complex 17 (CC17). Findings: From the 350 specimens investigated, 67 (19.1%) specimens were positive for VRE [95% confidence interval (CI): 15.0–23.2]. The prevalence of VRE colonization among CUH patients tested in this study ( N = 194) was 31.4% (95% CI: 24.7–38.1). By contrast, the general practitioner patient samples ( N = 29) showed a prevalence of 0%, whereas 22.2% of samples from other hospitals ( N = 27) were positive for VRE. All isolates were Enterococcus faecium (VRE fm ) and were indicated to contain CC17, though with considerable heterogeneity among the isolates. Conclusion: This high prevalence goes some way towards providing an explanation for the current high rates of VRE bacteraemia in Ireland, as well as highlighting the benefits of screening and enhanced infection control practices by all hospitals to control the high rates of VRE observed.